Perbedaan Pandangan dalam Pernikahan Dini antara Ulama Klasik dengan Ulama Kontemporer - Dedi Setiawan (Justicia Religia, 2025)
Early marriage is a social phenomenon that remains prevalent, particularly in developing countries such as Indonesia. This practice has sparked debates among scholars, especially between classical and contemporary Islamic scholars. Classical scholars generally allow early marriage based on Qur’anic verses, prophetic traditions, and the practices of the early Muslim generations, provided that the essential pillars and conditions of marriage are fulfilled. In contrast, contemporary scholars emphasize the approach of maqāṣid al-sharī‘ah, which focuses on welfare, health, and psychological readiness of the spouses, thereby tending to reject or restrict early marriage practices. This study aims to analyze the differences in perspectives between the two groups of scholars through a literature review. The analysis shows that classical scholars focus more on the legality of the marriage contract, while contemporary scholars take into account the social, educational, and health impacts. These differences are reflected in modern legal regulations, including Indonesian positive law, which sets the minimum age for marriage at 19 years. Thus, this divergence highlights the dynamic nature of Islamic jurisprudence and the necessity of contextualizing Islamic law to meet the needs of modern society.